2013
DOI: 10.1128/aem.03823-12
|View full text |Cite
|
Sign up to set email alerts
|

Cooccurrence of Free-Living Amoebae and Nontuberculous Mycobacteria in Hospital Water Networks, and Preferential Growth of Mycobacterium avium in Acanthamoeba lenticulata

Abstract: The incidence of lung and other diseases due to nontuberculous mycobacteria (NTM) is increasing. NTM sources include potable water, especially in households where NTM populate pipes, taps, and showerheads. NTM share habitats with free-living amoebae (FLA) and can grow in FLA as parasites or as endosymbionts. FLA containing NTM may form cysts that protect mycobacteria from disinfectants and antibiotics. We first assessed the presence of FLA and NTM in water and biofilm samples collected from a hospital, confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 46 publications
(55 reference statements)
3
64
0
2
Order By: Relevance
“…Vermamoeba vermiformis is one of the most common FLA to have been isolated from different water systems (Rhoads et al 2015;Montalbano Di Filippo et al 2015;Lu et al 2015;Armand et al 2016). It is also frequently recovered from hospital water networks as shown by several authors (Rohr et al 1998;Thomas et al 2006;Ovrutsky et al 2013;Pagnier et al 2015). Acanthamoeba, another genus of FLA commonly found in soil and water, has, as V. vermiformis, a two-staged life cycle: an actively feeding, dividing trophozoite form corresponding to the period of metabolic activity of the amoeba and a dormant cyst that can resist hostile environmental conditions such as nutrient depletion, osmotic stress, temperature changes, pH variations and water disinfection (Critchley and Bentham 2009;Fouque et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Vermamoeba vermiformis is one of the most common FLA to have been isolated from different water systems (Rhoads et al 2015;Montalbano Di Filippo et al 2015;Lu et al 2015;Armand et al 2016). It is also frequently recovered from hospital water networks as shown by several authors (Rohr et al 1998;Thomas et al 2006;Ovrutsky et al 2013;Pagnier et al 2015). Acanthamoeba, another genus of FLA commonly found in soil and water, has, as V. vermiformis, a two-staged life cycle: an actively feeding, dividing trophozoite form corresponding to the period of metabolic activity of the amoeba and a dormant cyst that can resist hostile environmental conditions such as nutrient depletion, osmotic stress, temperature changes, pH variations and water disinfection (Critchley and Bentham 2009;Fouque et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…We have not studied 21 and M avium . 22 Interestingly, it was shown that M tuberculosis is an amoeba-resistant pathogen and can survive into amoeba cytoplasmic vacuoles. 23 Th e discovery that MDR-TB isolates were present in 3.6% of samples is an alarming sign for communities with a high burden of MDR-TB, which needs prompt global attention.…”
Section: Discussionmentioning
confidence: 99%
“…Other species might be used but the protocol and broth should be adapted. It has been recently demonstrated that A. lenticulana (ATCC 30841) can be used in the same conditions as A. castellanii or A. polyphaga but has different susceptibility to infection 42 . To prevent encystment, it is important to use a relatively low incubation temperature (below 30 °C) and to maintain a humidified atmosphere.…”
Section: Discussionmentioning
confidence: 99%